2012
DOI: 10.1111/j.1349-7006.2012.02337.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Antitumor activity of human γδ T cells transducted with CD8 and with T‐cell receptors of tumor‐specific cytotoxic T lymphocytes

Abstract: The difficulty in the induction and preparation of a large number of autologous tumor-specific cytotoxic T lymphocytes (CTL) from individual patients is one of major problems in their application to adoptive immunotherapy. The present study tried to establish the useful antitumor effectors by using cd T cells through tumorspecific TCRab genes transduction, and evaluated the efficacy of their adoptive transfer in a non-obese diabetic/severe combined immunodeficiency (NOD/SCID) mice model. The TCRab gene was clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It was shown that γ/δ T cells – retrovirally transfected with α/β TCR against e.g. CMV or a tumor antigen- were highly functional in vitro [23] and in mice [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that γ/δ T cells – retrovirally transfected with α/β TCR against e.g. CMV or a tumor antigen- were highly functional in vitro [23] and in mice [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-expanded γδ T cells generating more effector T cells may release greater amounts of cytokine, and may immediately induce cytotoxicity functions [ 29 ]. Hanagiri [ 30 ] et al stated that, when γδ T cells expressed specific αβ TCR molecules in addition to γδ TCR, they were more effective in NSCLC patients. NK are the innate effector cells of immune response to pathogens and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies are highly relevant for the development of novel ACT strategies that exert superior antineoplastic activity. Along similar lines, the discovery that γδ T cells also mediate potent antitumor effects upon re-infusion (following “conventional” expansion/activation only or in combination with the retroviral transduction of CD8 plus a tumor-reactive αβ TCR) paves an interesting avenue for the development of innovative ACT protocols 128 - 131 …”
Section: Literature Updatementioning
confidence: 99%